The Research of Performance Comparison of Displacement and Mixing Ventilation System in Catering Kitchen - Yuan, Jianping; Wang, Longyan; Liu, Xiaofan (Scientific Research, 2013)
A commercial kitchen is a complicated environment where multiple components of a ventilation system including hood exhaust, conditioned air supply, and makeup air systems work together but not always in unison. And the application of an appropriate ventilation system is extremely vital to keep the catering kitchen comfortable, which consequently promotes the productivity and gains. Application of two systems (traditional mixing ventilation system and thermal displacement ventilation system) is compared in a typical kitchen environment using computational fluid dynamics modeling which was used to investigate the difference between mixing and displacement ventilation (DV). It was reported in two parts, one on thermal comfort and the other one on indoor air quality. The results show that DV can maintain a thermally comfortable environment that has a low air velocity, a small temperature difference between the head and ankle level, and a low percentage of dissatisfied people, and may provide better IAQ in the occupied zone. So it was persuasive that using thermal displacement ventilation in kitchen environment allows for a reduction in space temperature without increasing the air-conditioning system capacity.
Keywords: Kitchen; Displacement Ventilation; Mixing Ventilation; Numerical Simulation